Allogeneic HSCT for Autoimmune Diseases: A Retrospective Study From the EBMT ADWP, IEWP, and PDWP Working Parties - Greco, Raffaella; Labopin, Myriam; Badoglio, Manuela; Veys, Paul; Furtado Silva, Juliana M.; Abinun, Mario; Gualandi, Francesca; Bornhauser, Martin; Ciceri, Fabio; Saccardi, Riccardo; Lankester, Arjan; Alexander, Tobias; et al. (Frontiers in Immunology, 2019)
Background: This retrospective study assessed the use and long-term outcome of allogeneic hematopoietic stem cell transplantation (HSCT) in patients with severe autoimmune diseases (ADs), reported to the European Society for Blood and Marrow Transplantation (EBMT) registry. Methods: Between 1997-2014, 128 patients received allogeneic HSCT for various hematological (n=49) and non-hematological (n=79) refractory ADs. The median age was 12.7 years (0.2-62.2). Donors were syngeneic for 7, matched related for 46, unrelated for 51, haploidentical for 15 and cord blood for 9 patients. Results: The incidence of grades II-IV acute graft-versus-host disease (GvHD) was 20.8% at 100 days. Cumulative incidence of chronic GvHD was 27.8% at 5-years. Non-relapse mortality (NRM) was 12.7% at 100-days. Overall survival (OS) and Progression-Free Survival (PFS) were 70.2% and 59.4 % at 5-years respectively. By multivariate analysis, age less than 18 years, males, and more recent year of transplant were found to be significantly associated with improved PFS. Reduced conditioning intensity was associated with a lower NRM. On a subgroup of 64 patients with detailed information a complete clinical response was obtained in 67% of patients at one-year. Conclusions: This large EBMT survey suggests the potential of allogeneic HSCT to induce long-term disease control in a large proportion of refractory ADs, with acceptable toxicities and NRM, especially in younger patients.